2021
DOI: 10.3390/nu13113996
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial Analysis of Food Deserts and Their Impact on Health Outcomes in Children with Cystic Fibrosis

Abstract: Food insecurity (FI) is defined as “the limited or uncertain access to adequate food.” One root cause of FI is living in a food desert. FI rates among people with cystic fibrosis (CF) are higher than the general United States (US) population. There is limited data on the association between food deserts and CF health outcomes. We conducted a retrospective review of people with CF under 18 years of age at a single pediatric CF center from January to December 2019 using demographic information and CF health para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…24 Other studies have identified the significance of health impacts from social challenges such as food insecurity status and the economic implications of the COVID-19 pandemic for patients and families. 25,26 The current approaches shared by clinicians in this study provide insights on the importance of structure and guidance for clinicians to help support families. It also emphasizes the need for clinicians to actively adapt to address family needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Other studies have identified the significance of health impacts from social challenges such as food insecurity status and the economic implications of the COVID-19 pandemic for patients and families. 25,26 The current approaches shared by clinicians in this study provide insights on the importance of structure and guidance for clinicians to help support families. It also emphasizes the need for clinicians to actively adapt to address family needs.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study involving family based experience surveys found families value collaborative care with their clinical teams, suggesting some congruence of family perspectives as found in our study of clinicians 24 . Other studies have identified the significance of health impacts from social challenges such as food insecurity status and the economic implications of the COVID‐19 pandemic for patients and families 25,26 . The current approaches shared by clinicians in this study provide insights on the importance of structure and guidance for clinicians to help support families.…”
Section: Discussionmentioning
confidence: 99%
“…Our results highlight important barriers to optimal adherence to CF dietary recommendations that can be exacerbated by FI, including cost of food, increased caloric requirements, single income household, transportation, and cost of housing, utilities, and healthcare. A recent study by our team showed that people with CF living in and near food deserts, a risk factor for FI, had increased odds of with a non-ideal lower BMI or weight-for-length [12]. It has also been noted that FI contributes to greater healthcare costs and financial strain, particularly when looking at patients with chronic disease [17].…”
Section: Discussionmentioning
confidence: 99%
“…As such, the CF Foundation (CFF) recommends an intake of at least 500 calories per day over the standard daily requirement with fat intake composing about 35-40% of those calories [6][7][8]. Given that people with CF have increased caloric demands, FI may contribute to the inability to achieve and maintain appropriate weight gain and lead to malnutrition in CF and is a nutritional risk factor for the CF population [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%